Electrical measuring instruments and measurements - Bhargava, S. C. (India : BS, 2013)
This book underlines the importance of quantitative knowledge and of acquiring experience in conducting measurements, as much as the inevitable role of accuracy and error. With a pleasant presentation style, this book provides a complete learning module on the topic.
Units, dimensions and standards -- Magnetism, electricity and electromagnetism -- Electical circuit analysis -- Visual display and analyses -- Measuring instruments -- Extension of instruments range: current and potential transformers - Measurement of power -- Measurement of energy -- Potentiometers -- Measurement of resistance -- AC and DC bridges and bridge methods -- Magnetic measurements -- Measurement of non-electrical quantities.
Includes bibliographical references and index.
Keywords: Measuring instruments; Electric measurements; Electronic instruments; Electronic measurements